Supply chain management practices and performance measures : case evidence from Malaysian automotive manufacturers / Eley Suzana Kasim - Kasim, Eley Suzana (Institute of Graduate Studies, UiTM, 2014)
It has been noted that businesses seek to capitalize on their supply chain resources and capabilities as a way to achieve competitive advantage. From a competitive advantage viewpoint, supply chain management (SCM) has been widely advocated as a potential competitive management tool that contributes to firm performance, particularly in the automotive industry, the focus of this study. This industry is important because automotive firms are constantly responding to the changes following the environmental forces of globalization. A possible opportunity for advancement of SCM as a competitive management tool is the potential contribution of management accounting (MA) in utilizing SCM as a value creation tool. However, this is largely neglected in the literature. Furthermore, the shift towards value creation within SCM is consistent with recent developments in management accounting.